Single-atom platinum with asymmetric coordination environment on fully conjugated covalent organic framework for efficient electrocatalysis - Zhang, Ziqi; Zhang, Zhe; Chen, Cailing; Wang, Rui; Xie, Minggang; Wan, Sheng; Zhang, Ruige; Cong, Linchuan; Lu, Haiyan; Han, Yu; Xing, Wei; Shi, Zhan; et al. (Nature communications, 2024)
Two-dimensional (2D) covalent organic frameworks (COFs) and their derivatives have been widely applied as electrocatalysts owing to their unique nanoscale pore configurations, stable periodic structures, abundant coordination sites and high surface area. This work aims to construct a non-thermodynamically stable Pt-N 2 coordination active site by electrochemically modifying platinum (Pt) single atoms into a fully conjugated 2D COF as conductive agent-free and pyrolysis-free electrocatalyst for the hydrogen evolution reaction (HER). In addition to maximizing atomic utilization, single-atom catalysts with definite structures can be used to investigate catalytic mechanisms and structure-activity relationships. In this work, in-situ characterizations and theoretical calculations reveal that a nitrogen-rich graphene analogue COF not only exhibits a favorable metal-support effect for Pt, adjusting the binding energy between Pt sites to H* intermediates by forming unique Pt-N 2 instead of the typical Pt-N 4 coordination environment, but also enhances electron transport ability and structural stability, showing both conductivity and stability in acidic environments. In addition to maximizing atomic utilization, single-atom catalysts with defined structures can be used to investigate catalytic mechanisms and structure-activity relationships. Here, authors study a non-thermodynamically stable Pt-N 2 active site for the electrochemical hydrogen evolution reaction.